Crinkleroot's guide to knowing the birds - Arnosky, Jim. (New York : Aladdin Paperbacks, 1997)
An introduction to birds one might see in the woods.
"Aladdin picture books"--Cover.
Wilson's Children
Elem. School Library Collection
School Library Journal
5.4
K-3
Keywords: Birds -- Juvenile literature; Birds -- Identification -- Juvenile literature; Birds; Birds -- Identification; Birds; Birds -- Identification